Minuman Fungsional Instan dengan Kombinasi Kopi Robusta (Coffea canephora), Ekstraksi Gambir (Uncaria gambir Roxb.) dan Ginseng (Panax quinquefolius L.) - Erna Yusnina Eka Putri; Budi Santoso; Agus Wijaya (Seminar Nasional Lahan Suboptimal, 2021)
Putri EYE, Santoso B, Wijaya A. 2021. Instant functional drink with robusta coffee combination (Coffea canephora), extracted gambir (Uncaria gambir Roxb.) and ginseng (Panax quinquefolius L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021, pp. 89-100. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purpose of this study was to determine the effect of increasing the concentration of gambir on the physical, chemical, and antioxydant activity of instant functional drinks from a combination of robusta coffee, gambir extract and ginseng. This study used a non-factorial Completely Randomized Design (CRD) with the treatment of  formulation of mixed instan powder of robusta coffee and ginseng : gambier extract (F) consisting of 6 levels of treatment and 3 repetitions. Each formulation is as follows; F1 = 97.5%  instant powder of coffee-ginseng : 2.5% gambier extract, F2 = 95% instant powder of coffee-ginseng : 5% gambir extract, F3 = 92.5% instant powder of coffee-ginseng : 7.5% gambier extract, F4 = 90% instant powder of coffee-ginseng : 10% gambier extract, F5 = 87.5% instant powder of coffee-ginseng : 12.5% gambier extract, and F6 = 85% instant powder of coffee-ginseng : 15% extract gambier. The observed parameters are solubility rate, water content, pH value, antioxidant activity and caffeine analysis. The results showed that the formulation treatment of mixed instan powder of robusta coffee and ginseng : gambier extract significantly affected the solubility rate, water content, pH value, and antioxidant activity. The highest value for antioxidant activity (IC50) was 87.46 ppm. The lowest water content was 7.10%, the dissolution rate was 26.78 seconds, the highest pH value was at 5.68, and the caffeine content was 1.26%.